2005
DOI: 10.1128/mcb.25.7.2795-2807.2005
|View full text |Cite
|
Sign up to set email alerts
|

Control of Mammalian Circadian Rhythm by CKIε-Regulated Proteasome-Mediated PER2 Degradation

Abstract: The mammalian circadian regulatory proteins PER1 and PER2 undergo a daily cycle of accumulation followed by phosphorylation and degradation. Although phosphorylation-regulated proteolysis of these inhibitors is postulated to be essential for the function of the clock, inhibition of this process has not yet been shown to alter mammalian circadian rhythm. We have developed a cell-based model of PER2 degradation. Murine PER2 (mPER2) hyperphosphorylation induced by the cell-permeable protein phosphatase inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
456
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 447 publications
(486 citation statements)
references
References 54 publications
19
456
1
Order By: Relevance
“…Proteolysis is also a theme shared by circadian rhythms and cell cycle regulation, providing a driving force for regulated transitions between distinct states (e.g., dark and light, metaphase and anaphase). Targeted proteolysis of Per and Tim proteins appears to ensure the maintenance of circadian rhythm in several organisms (Hunt and Sassone-Corsi 2007;Eide et al 2005). Similarly, the anaphase promoting complex/ cyclosome (APC/C) is an E3 ubiquitin ligase complex that triggers the metaphase-anaphase transition by dissolving the connections between sister chromatids after chromosome congression is complete (S. Kim and Yu 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Proteolysis is also a theme shared by circadian rhythms and cell cycle regulation, providing a driving force for regulated transitions between distinct states (e.g., dark and light, metaphase and anaphase). Targeted proteolysis of Per and Tim proteins appears to ensure the maintenance of circadian rhythm in several organisms (Hunt and Sassone-Corsi 2007;Eide et al 2005). Similarly, the anaphase promoting complex/ cyclosome (APC/C) is an E3 ubiquitin ligase complex that triggers the metaphase-anaphase transition by dissolving the connections between sister chromatids after chromosome congression is complete (S. Kim and Yu 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Among the multiple molecular mechanisms that influence the period of circadian rhythms, a major role is played by those that control clock protein degradation (Liu et al 2000;Eide et al 2005;Gallego et al 2006;Busino et al 2007;Reischl et al 2007). Here we compared three minimal models proposed for circadian clocks, showed that they predict opposite profiles of period as a function of the clock protein degradation rate, and indicated how to reconcile these contradictory predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, PER and CRY levels are higher during the day and lower at night, similar to the SCN neural activity rhythm. The circadian time course of gene expression is regulated by post-translational mechanisms, including phosphorylation-dependent ubiquitination and proteosomal degradation of PER and CRY proteins in the cytoplasm (36)(37)(38)(39)(40) , allowing for a new cycle of transcription by relieving inhibition of the BMAL1:CLOCK/NPAS2 transcriptional complex.…”
Section: Regulation Of Clock-controlled Genes Involved In Lipid Metabmentioning
confidence: 99%